Internationalization activities in Malaysia: Profile of logistics operators in Malaysia - Ahmad, Sa'ari; Ahmad, Fais; Ahmad Fawzi, Dzulhilmi (2016)
The empirical results presented in this report focused on the companies that were involved in logistics activities in Malaysia. More specifically, the study attempts to investigate the profile of logistics operators in Malaysia. The data for the study was collected through 400 mail questionnaires send to the selected logistics companies.Two hundred companies responded by returning the questionnaires.Only 125 were fully completed used in the analysis.The findings clearly indicates that the industry was dominated by various ethnic with different level of educations and various legal form of business. The industries offers various kinds of employment opportunities and became the catalyst to economic development and international trade opportunities for the Nation